Sustainability and distance learning: a diverse European experience?. (4th May 2017) - Bell, Simon; Douce, Chris; Caeiro, Sandra; Teixeira, Antonio; Martín-Aranda, Rosa; Otto, Daniel
ABSTRACT: Higher Education (HE) is experiencing disruption from technologies, demographics, the globalising world and longer life expectancy. Historically Higher Education has had a legacy of being seen as the requirement for an educated 'elite', there has been a policy ambition set in various countries (including the UK) for it to become the expectation for much wider segments of the population as a whole. As students become 'everyone' and learning becomes 'all the time' Distance Teaching and Research Institutions have a tremendous opportunity but there are also many disruptions and barriers to overcome. Higher Education institutions have an important role within Education for Sustainable Development and sustainable lifestyles; one of the important goals and targets of the United Nations Sustainable Development goals for 2030. Higher Education can contribute to sustainability in many ways – social, technical and environmental; globally and locally. In particular distance-learning universities due to the flexibility in the learning process, use of technologies, and inter-disciplinary approach to teaching and learning, constitute key factors in education for sustainable development. But what will this contribution look like? In this paper, the responses from senior leaders in four major European distance-learning universities are presented, compared and discussed. The tentative conclusions draw out some strategic imperatives for sustainable higher education in the twenty first century.